Pharyngeal Reconstruction Methods to Reduce the Risk of Pharyngocutaneous Fistula After Primary Total Laryngectomy: A Scoping Review (2023)
ABSTRACT: Introduction: The most common early postoperative complication after total laryngectomy (TL) is pharyngocutaneous fistula (PCF). Rates of PCF are higher in patients who undergo salvage TL compared with primary TL. Published meta-analyses include heterogeneous studies making the conclusions difficult to interpret. The objectives of this scoping review were to explore the reconstructive techniques potentially available for primary TL and to clarify which could be the best technique for each clinical scenario. Methods: A list of available reconstructive techniques for primary TL was built and the potential comparisons between techniques were identified. A PubMed literature search was performed from inception to August 2022. Only case-control, comparative cohort, or randomized controlled trial (RCT) studies were included. Results: A meta-analysis of seven original studies showed a PCF risk difference (RD) of 14% (95% CI 8-20%) favoring stapler closure over manual suture. In a meta-analysis of 12 studies, we could not find statistically significant differences in PCF risk between primary vertical suture and T-shaped suture. Evidence for other pharyngeal closure alternatives is scarce. Conclusion: We could not identify differences in the rate of PCF between continuous and T-shape suture configuration. Stapler closure seems to be followed by a lower rate of PCF than manual suture in those patients that are good candidates for this technique.